Encoding and decoding of serially concatenated codes for data storage systems - Yin, Ke. (2013)
In this project, we consider the application of serially concatenated codes (SCC) for data storage systems. The SCC typically consists of an outer code and an inner code. The outer code of the SCC can be a high-rate convolutional code, or a low-density parity-check (LDPC) code; while the inner code normally takes the form of the accumulate code or a high-rate recursive convolutional code (RSC). The SCC has the advantage of achieving flexible code rates, low encoding complexities and various decoding schedules, which makes it a promising channel coding scheme for data storage systems. Considering that the conventional LDPC codes have some limitations for applications to high-rate magnetic recording channels, such as high encoding complexities and the lack of sufficient flexibilities in terms of code lengths or code rates, we consider extended irregular-accumulate (eIRA) codes in this project which are flexible in code parameters and feature linear-time encoding complexities.